Komputerowe modelowanie ewolucji języka - Lipowska, Dorota (Wydawnictwo Naukowe UAM, 2016)
The present monograph belongs to the interdisciplinary scientiﬁc ﬁeld of language evolution. It is mainly concerned with the application of computational modelling to study the origin and change of language. Computer simulations of models called language games, implemented as multiagent systems, enable us to examine how a population of individuals can reach a consensus on some linguistic conventions, for example, names. This process, fundamental for the emergence of language, is spontaneous and takes place without any external control or steering. The emergence of language is thus a global consequence of local interactions between individuals. Computational modelling turns out to be research tool extremely well-suited to studying some aspects of language structure and processes, such as diversiﬁcation of languages and their extinction. It might even shed some light on the intricate inﬂuence of our language on the biological evolution of humans. Keywords: language evolution; evolutionary linguistics; computer modelling; language games; naming game; agent models.

Jak powstał język – ten unikalny, charakterystyczny dla człowieka system komunikacji? Badaniem tego zagadnienia zajmuje się stosunkowo nowa, lecz prężnie się rozwijająca nauka: ewolucja języka. Jest to interdyscyplinarna dziedzina, integrująca wiedzę różnych nauk o człowieku, jego biologii, kulturze i języku, korzystająca również z osiągnięć nauk przyrodniczych i ścisłych. Niniejsza monografia przedstawia zastosowanie modelowania komputerowego do badania zagadnienia powstania i rozwoju języka, w szczególności zaś wykorzystanie do tego celu gier językowych oraz systemów wieloagentowych. Przeprowadzając komputerowe symulacje, bada się, w jaki sposób populacja odrębnych osobników nie dysponujących jeszcze wspólnym językiem, wyłącznie w toku wzajemnych interakcji komunikacyjnych, jest w stanie osiągnąć konsensus co do stosowanego w całej populacji zestawu lingwistycznych konwencji, np. nazw. Zalążek języka wyłania się więc tu jako konsekwencja oddziaływań między osobnikami. Modelowanie komputerowe jest znakomitym narzędziem do badań tego rodzaju zjawisk.
Computational modelling of language evolution
Keywords: ewolucja języka; lingwistyka ewolucyjna; modelowanie komputerowe; gry językowe; gra w nazywanie; modele agentowe